First record of Herpetogramma phaeopteralis (Guenée, 1854) (Lepidoptera: Crambidae) from Iraq - Muslim Ashor Al-Etby (Kufa Journal for Agricultural Sciences)
The study was carried out to report the new recorded genus Herpetogramma (Crambidae: Lepidoptera). A full description of the genus including, larva, pupa, and adult (antennae, labial palps, proboscis, tarsal seta end as well as wing venation) was used. A program of ImageJ for measurement was also used. The aim of the current study was to diagnose the species H. phaeopteralis (Crambidae: Lepidoptera), which is first recorded attacking turf grass of a football stadium in Basrah province, Iraq and to update our knowledge with recently collected data on the fauna of Crambidae of Iraq.